MECHANISM OF CRISIS MANAGEMENT TO ENSURE THE ENTERPRISE ECONOMIC SECURITY (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The article demonstrates the existence of various types of crisis situations at most domestic enterprises. The theoretical and methodological basis of crisis management to ensure the enterprise economic security is considered. The main objective of crisis management, as well as of economic security management, is the protection against external and internal threats the enterprise may face. Management process involves the regulation of crisis and risk situations, their prevention and overcoming of negative social and economic consequences in case they do occur.The mechanism of crisis management for economic security is defined as a combination of organizational and economic measures such as methods, tools and levers operating in the legal framework which aim at predicting, preventing, minimizing or eliminating external and internal threats to the enterprise.The factors leading to the enterprise crisis are systematized. The principles of effective crisis management to ensure economic security are given. The main principles include: timely diagnosis of crisis situations at the enterprise; the speed of response to crisis phenomena (decision-making efficiency); identification and use of internal opportunities to prevent crisis or recover from it; compliance with legislation and ethical standards in substantiating anti-crisis measures.The sequence of crisis management stages is determined, thus promoting a high level of economic security: to carry out a comprehensive diagnostics of the external and internal environment of the enterprise; to identify the causes of the crisis and the level of threats; to validate the anti-crisis strategy; to develop the system of anti-crisis plans, projects, and programs; to develop anti-crisis measures; to select methods, tools and levers of crisis management; to control anti-crisis measures; to assess the enterprise operation security level. Compliance with crisis management principles and consistency will contribute to the safe development of the enterprise.The model of behavior and anti-crisis measures for safe development restoration depending on the scope of crisis are determined. Particular attention is paid to the study of peculiarities of the enterprise anti-crisis strategies development and implementation.
Keywords: crisis, crisis management, economic security, threats, mechanism, anti-crisis strategy.